Investigating parental factors that lead to adolescent Internet Gaming Addiction (IGA) - Huazhen Li; Kangzhou Peng; Yi Wu; Linna Wang; Zhanni Luo (PLoS ONE, 2025)
Internet gaming addiction (IGA) has become a common phenomenon that affects adolescents, due to its possible negative effects on physical and mental health issues. However, very few studies have particularly examined the relationship between adolescent game addiction and parental influences. In this study, we address some undesirable parental behaviors and aim to explore whether they influence adolescents’ internet gaming behaviors. A total of 315 adolescents who have exposed to Internet games participated in this study. We examined the relationship between four parental factors and the development process examined by the structural equation modeling (SEM) techniques: adolescent Internet gaming addiction (IGA), parental interpersonal conflict (PIC), parental loneliness (PL), parental phubbing (PP), and parental rejection (PR). We proposed nine hypotheses, five of which were supported by the data. The results suggested that parental loneliness leads to parental phubbing and rejection behaviors, as well as enhancing Internet gaming addiction among adolescents. Additionally, parental interpersonal conflict can cause parental loneliness. However, the study found that parental loneliness, parental rejection, and parental interpersonal conflict do not statistically significant impact on adolescents’ internet gaming behaviors.